(untitled) (Global Journal of Science Frontier Research, 2021)
The plant latex consist of biologically active compounds useful for diverse health benefits and could be a potential source of unique proteases. Proteases play key roles in the regulation of biological processes in plants and currently have become a vital part of the food and feed industry. In order to understand the underlying mechanisms of action of unique plant latex, the present study isolate and characterized a protease enzyme from the crude latex of plantain plant. Crude latex collected from different parts (leaves, stem, trunk and branches) of the plantain plant was centrifuge to separate the supernatant from any particles. The supernatant was used as the crude latex extract for the research. A protease enzyme was isolated from the crude latex extract and the effect of pH, temperature, incubation time, kinetic study of the protease activity as well as protein were determined spectrophoto-metrically. The enzyme protease was found to have a 9.84 mg/ml of protein with a specific activity of 3.06 unit/mg protein respectively.